2003
DOI: 10.1016/s0378-1097(03)00051-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mechanisms involved in phagocytosis of Legionella pneumophila by human cells

Abstract: Legionella pneumophila, the causative agent of Legionnaires' disease, is able to survive and multiply efficiently in a variety of mammalian cells. By using in vitro assays, the uptake of L. pneumophila into monocytes has shown to be mediated, at least in part, through attachment of complement-coated bacteria to complement receptors, but complement-independent phagocytosis could also be demonstrated. Since complement levels in the human lung are normally low, the role of complement-dependent phagocytosis in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…However, recent studies have shown that L. pneumophila replicates also in human alveolar epithelial cells [5,6]. Although Legionella less efficiently replicates within human T cells compared with macrophages [7], little is known of the consequences of T cell infection with Legionella .…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that L. pneumophila replicates also in human alveolar epithelial cells [5,6]. Although Legionella less efficiently replicates within human T cells compared with macrophages [7], little is known of the consequences of T cell infection with Legionella .…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of opsonin-dependent phagocytosis to L. pneumophila infection is also dubious, given that complement levels in the lungs are generally very low (274). In addition, the phagocytosis of L. pneumophila is clearly observed in the absence of serum and occurs in cells that express complement receptors at only low levels (146,281,354). Furthermore, the ability of L. pneumophila to invade nonprofessional phagocytes such as A549, CHO-K1, and HeLa epithelial cells supports the hypothesis that the uptake of L. pneumophila is a virulence-directed property of the pathogen (112,139,222,250).…”
Section: Bacterial Entry and Exitmentioning
confidence: 63%
“…The expression of CD15 was decreased during differentiation with TGFβ and calcitriol, but was not influenced by miRNA-328 knockdown. Finally, we measured CD11b expression which represents a marker for mature myeloid cells29. The analysis revealed a strong upregulation of the CD11b marker during MM6 cell differentiation which was significantly reduced by miRNA-328 knockdown (Fig.…”
Section: Resultsmentioning
confidence: 98%